2018
DOI: 10.1007/s11010-018-3398-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anticancer effects of p-methoxycinnamic acid, an active phenylpropanoid, against 1,2-dimethylhydrazine-induced rat colon carcinogenesis

Abstract: p-methoxycinnamic acid (p-MCA) is an active phenolic acid found in rice bran, turmeric, brown rice, Kaempferia galanga, buckwheat inflorescence, etc. Earlier, we have reported that p-methoxycinnamic acid possesses antioxidant and antilipidperoxidative effects on 1,2-dimethylhyrdrazine (DMH)-induced colon carcinogenesis. The purpose of this study is to unravel the anti-inflammatory and anticancer properties of p-MCA against DMH-induced colon carcinogenesis. Male albino Wistar rats were randomly divided into six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…30 Studies have demonstrated that rice bran extracts and FRB serve critical roles in the regulation of oxidative response, inammatory reaction, immune function, cholesterol metabolism, and tumor suppression. [31][32][33] In this study, we emphasized the potential function of rice bran extracts and FRB in cancer prevention and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…30 Studies have demonstrated that rice bran extracts and FRB serve critical roles in the regulation of oxidative response, inammatory reaction, immune function, cholesterol metabolism, and tumor suppression. [31][32][33] In this study, we emphasized the potential function of rice bran extracts and FRB in cancer prevention and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The data presented in Table 1 indicate a number of anticancer properties of methoxy derivatives of cinnamic acid [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Of particular interest seems to be the anticancer activity of p -MCA acid, which against colon cancer cells (HCT-116) is similar to doxorubicin.…”
Section: Biological Activity Of Methoxylated Derivatives Of Cinnamic Acidmentioning
confidence: 99%
“…3 No ACF observed. 4 All rats were administered with DMH/DSS. C, AIN-93G diet; D, AIN-93G containing 10% djulis; DLA, AIN-93G containing 10% djulis + 5 × 10 6 cfu L. acidophilus/g; DHA, AIN-93G containing 10% djulis + 5 × 10 7 cfu L. acidophilus/g.…”
Section: Acf In the Colonmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) mediates inflammation and plays an important role in CRC. Increased COX-2 expression has been detected in both colorectal tumor-bearing animals [4] and CRC patients [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation